Antimicrobial activity and toxicity of Musa brachycarpa peel extracts for evaluation of cosmetic formulation - Maarof, Mas Haidatul Aqma (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Banana peels extracts have been used to promote wound healing mainly from bums and to prevent a substantial number of illnesses. This study aimed to evaluate the antibacterial activity and toxicity of cosmetic cream containing Musa brachycarpa (MB) peels extracts. The antibacterial activity of both aqueous and methanol extracts of Musa brachycarpa peels against Staphylococcus aureus (ATCC25923) and Staphylococcus epidermidis (A TCC 14990) was carried out using the disk diffusion and microbroth dilution methods. The aqueous extract of MB peel did not show inhibitory effect against the tested isolates. However methanol extract showed highest inhibitory effect against S. epidermidis with 14 mm inhibition zone diameter, followed by S. aureus with diameter of 12mm at 40mg/disc. Methanol extract of banana peels displayed a better antibacterial activity against both S. aureus and S. epidermidis compared to aqueous extract. Cream formulation shows inhibition in microbial growth with 10 mm inhibition against S.aureus and 12 mm against S. epidermidis. The MIC values of methanol extract against S. aureus and S. epidermidis were 80mg/ml. While the MIC value for aqueous extract was undetermined. The MBC values of methanol extract against S. aureus and S. epidermidis were 160 mg/ml each. Cytotoxic assay of the extracts was conducted using "Brine Shrimp Lethality" test (BLST). Methanol and aqueous extracts did not induce significant cytotoxic activity with LC50 value of 314.06 µg/mL and 604.98 µg/mL respectively after 24 hours. Heavy metal tests using atomic absorption spectroscopy (AAS) were performed to detect the presence of arsenic (As), lead (Pb), cadmium (Cd), chromium (Cr) and zinc (Zn) in the extracts and cosmetic cream. The level of heavy metals levels was within the acceptable range and safe to be used. This preliminary study has demostrated the antimicrobial potential and the safety of MB methanol extract to be applied for cosmetic use.